Gratitude as an Affective Foundation of Religiosity: Evidence from Indonesian Majelis Taklim Communities - Gilang Tri Prayogo Yusuf; Prahastia Kurnia Putri (Journal of Educational, Health and Community Psychology, 2026)
This study investigated the association between gratitude and religiosity among members of Islamic study groups (majelis taklim) in Indonesia. Using a quantitative cross-sectional design (N = 154), participants completed an 8-item Indonesian Gratitude Questionnaire derived from the GQ (McCullough et al., 2002) and its 11-item Indonesian adaptation (Grimaldy & Haryanto, 2020) and a modified 34-item Centrality of Religiosity Scale adapted for the Indonesian Islamic context (Huber & Huber, 2012; Purnomo & Suryadi, 2018). Simple linear regression examined the gratitude–religiosity relationship. Results showed gratitude was significantly associated with overall religiosity (β = .463, p < .001, 95% CI [1.11, 2.09]), explaining 21.4% of the variance (R² = .214). These findings suggest gratitude is meaningfully linked to religiosity in majelis taklim communities within collectivist Islamic contexts. Faith-based community programs and majelis taklim facilitators may consider integrating structured gratitude practices (e.g., brief reflective exercises, gratitude journaling, or group sharing) as a complementary strategy to strengthen religious engagement and social cohesion, while future studies should test causal mechanisms using longitudinal or intervention designs.